Servicescape, Lingkungan Sosial, Suasana Hati Pengaruhnya terhadap Perilaku Berbelanja Hedonis - Fatchur Rohman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research to examine the role of servicescape, social surrounding, and antecedent states influence to hedonic shopping behavior. The research samples are 100 people with convenience sampling’s method. To test hypotheses,this research uses multiple regression analysis. The research result shows that servicescape, social surrounding, and antecedent states affect to hedonic shopping behavior. The findings can improve situational factor to affect shopping behavior at apparel women shop. Such servicescape can design as like as beutique layout.Keywords: Servicescape, social surrounding, antecedent states, hedonic shopping behavior